Strategies for integral rehabilitation and improvement of the energy efficiency of Lagos Park building in Madrid - Maciá-Torregrosa, María Eugenia; Camacho-Diez, Javier; González-Lezcano, Roberto Alonso (Frontiers in Built Environment, 2023)
As a primary goal, Inadequate energy consumption and outdated construction systems are causing financial losses for homeowners. Spain's failure to meet European guidelines on CO2 emissions highlights the urgent need to address the energy inefficiency of buildings, responsible for 40% of such emissions. This article presents a comprehensive refurbishment project undertaken in the Lagos Park residential building in Madrid. The paper offers a detailed analysis of common building issues related to excessive humidity in the surrounding areas and deficiencies in the energy performance of the building envelope, including facades and roofs. Precise measures for achieving compliance with the Spanish Technical Building Code (CTE), as well as enhancing energy efficiency and functionality, are explained through the renovation of the building envelopes. The study also encompasses improvements made to the domestic hot water supply systems and the air-conditioning system, which contribute to the building's attainment of an optimal energy rating (energy Class A). The extensive renovation undertaken in the complex has transformed Lagos Park homes into "zero energy consumption" residences. The strategies employed, ranging from electrical appliances to the house's structural design, are all geared towards maximizing energy usage efficiency, resulting in significantly reduced monthly electricity bills by 65 to 75%.